JASALMA INTELLEKT JÁRDEMINDE JAZBA JUMÍSLARDÍ BAHALAWDÍŃ PEDAGOGIKALÍQ TIYKARLARÍ - Dauletiyarova, Nigora Kenesbaevna (ILIM hám JÁMIYET, 2026)
This article examines the pedagogical and psychometric foundations of assessing writing tasks using artificial intelligence. It explores the benefits and limitations of AI-based assessment systems, focusing on reliability, validity, fairness, and academic integrity. The study emphasizes the importance of combining AI capabilities with human expertise to promote critical thinking, student agency, and effective academic writing.